2019
DOI: 10.3390/pr7100718
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation Characteristic Research on the Load Vertical Vibration of a Hydraulic Automatic Gauge Control System

Abstract: As the core control system of a rolling mill, the hydraulic automatic gauge control (HAGC) system is key to ensuring a rolling process with high speed, high precision and high reliability. However, a HAGC system is typically a mechanical-electric-hydraulic coupling system with nonlinear characteristics. The vertical vibration of the load easily occurs during the working process, which seriously affects the stability of the system and the causes are difficult to determine. In this work, the theory and method of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…With the rapid development of computer technology, numerical simulation is increasingly widely used in the fluid flow [27][28][29][30][31][32][33]. Guelich et al [34] studied the effect of wall roughness on the efficiency Energies 2020, 13, 464 3 of 20 of centrifugal pumps.…”
Section: Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of computer technology, numerical simulation is increasingly widely used in the fluid flow [27][28][29][30][31][32][33]. Guelich et al [34] studied the effect of wall roughness on the efficiency Energies 2020, 13, 464 3 of 20 of centrifugal pumps.…”
Section: Literature Overviewmentioning
confidence: 99%
“…In terms of roughness, the total pressure loss value was reduced by 23.1% compared to the smooth blade. Han et al [26] used numerical methods to study the influence of blade surface roughness on the internal flow field and characteristic parameters of the compressor under the compressor-level environment and found that the blade roughness had a significant effect on the main performance parameters of the compressor; with the blade roughness with the increase of the compressor, the performance degradation of the compressor stage was intensified, and the energy loss of the internal airflow was increased, especially the energy loss of the airflow near the middle and upper part of the leading edge of the impeller was severe, and the temperature of the blade end wall was increased.With the rapid development of computer technology, numerical simulation is increasingly widely used in the fluid flow [27][28][29][30][31][32][33]. Guelich et al [34] studied the effect of wall roughness on the efficiency Energies 2020, 13, 464 3 of 20 of centrifugal pumps.…”
mentioning
confidence: 99%
“…In recent years, hydraulic systems have been developing in the direction of lightweight, small volume, high-pressure, high power density, and variable pressure characteristics [2]. The complexity and automation level of hydraulic systems have been continuously improving [3]. As the heart of the hydraulic system, the running state of the hydraulic pump will directly affect the working state of the entire hydraulic system and even the industrial equipment as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure pulsation and unstable flow in the vane pump is mainly caused by the rotor-stator interaction between the pressure pulsation and unstable flow in the vane pump is mainly caused by the rotor-stator interaction between the impeller and the guide vane. These pulsations can sometimes be very severe and cause damage to the piping or other components in a pumping system, which may give rise to vibration [6][7][8][9], generate hydraulic noise [10][11][12], and affect the performance of the pumping system, thus affecting the stable operation of the pumping system. Therefore, the distribution of pressure pulsations in the pump needs to be studied to ensure the safe, efficient, and stable operation of the pumping station.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency amplitudes decrease from the impeller exit to the bulb unit.Processes 2019, 7, 949 2 of 11 impeller and the guide vane. These pulsations can sometimes be very severe and cause damage to the piping or other components in a pumping system, which may give rise to vibration [6][7][8][9], generate hydraulic noise [10][11][12], and affect the performance of the pumping system, thus affecting the stable operation of the pumping system. Therefore, the distribution of pressure pulsations in the pump needs to be studied to ensure the safe, efficient, and stable operation of the pumping station.With the development of computational fluid dynamics (CFD) technology, more scholars are using CFD to study complex flow fields in pumps [13][14][15], but the results of numerical simulation need to be verified by experimental data.…”
mentioning
confidence: 99%